Answer:
-6s-c+1
Step-by-step explanation:
(-3s-4c+1)+(-3s+3c)
We have been given the above expression. To find the sum, we simply collect the like terms and combine them;
(-3s-4c+1)+(-3s+3c) = -3s + -3s -4c + 3c + 1
-3s + -3s -4c + 3c + 1 = -3s - 3s + 3c - 4c + 1
-3s - 3s + 3c - 4c + 1 = -6s - c + 1
Therefore;
(-3s-4c+1)+(-3s+3c) = -6s-c+1
If there are 27 students in the class and they have to form as many groups of 4 as possible, you can calculate this using the following step:
27 / 4 = 6.75 = 6 3/4
Result: 27 students can form 6 groups of 4 students and 3 students have to form their own group.
Answer is 17.
Both values are given where:
a = 7 and b = 3
Substitute the values into the given expression.
( 2 x 7 ) + 3
14 + 3 = 17
Hope it helps :]